PUSAT KEBUGARAN DAN KESEHATAN DI BANJARBARU - Renaldy, Azriel; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Obesity and mental health disorders are closely related. Mental health disorders in obese people are usually caused by an unfavorable environment that causes obese people to often experience depression, anxiety, and post-traumatic stress disorder. By carrying out the concept of a healing environment , the Fitness and Health Center in Banjarbaru is an answer to the mental health issues experienced by the community. This area is an open space with several supporting facilities in the form of a gym center, health clinic, and healthy restaurant. The concept that is applied to the design uses 10 physical components of the environment as a reference in applying the concept of healing environment.